PERANG SOSOH DALAM MEMPERTAHANKAN KEMERDEKAAN DI DESA PEDEKIK KABUPATEN BENGKALIS PADA TAHUN 1949 - Nuryana Nuryana; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The independence achieved by the Indonesian people proclaimed on August 17, 1945, is not the end of the Indonesian struggle against Dutch colonialism. The Dutch returned to take control of Indonesia, so that the Indonesian nation still had to struggle to maintain the independence that had been achieved. This is evidenced by the existence of armed clashes, even in several cities suddenly become a battle, plus Dutch activities that carry out police actions that cause resistance in various regions, including Bengkalis. One of the events that happened in Bengkalis against the Dutch attack is known as the Sosoh War. The objectives of this study are (1) To find out the background of the arrival of the Dutch in Bengkalis Post Independence, (2) To find out the process of the Sosoh War in maintaining independence in the Pedekik Village of Bengkalis Regency in 1949, (3) To find out the end of the struggle of the TNI and troops Sabilillah after the Sosoh War in maintaining independence in the Pedekik Village of Bengkalis Regency in 1949, (4) To find out comparisons with the results of previous studies. The method used in this research is to use history methods with data collection techniques, namely interviews, observation, documentation and literature. The research location is in the Village of Pedekik. The results showed that the Sosoh War was a war between TNI and Sabilillah forces in the fight against the Dutch Military Aggression II in 1949 in the village of Pedekik. One of the physical struggles in dealing with the Netherlands was also carried out by a group of Islamic fighters, namely the Sabilillah Army. The Sosoh War in the Village of Pedekik resulted in a conflict between the Dutch and the Indonesian side, causing the nation’s warriors to die. As a nation's generation, we should respect and appreciate their services and not forget the history that exists in this country.Key Words: Village of Pedekik, Defending Independence, Sosoh War